Змістове наповнення поняття «обдарованість» у працях британських учених - Холод, Ірина (Studies in Comparative Education, 2014)
У статті розглянуто визначення поняття «обдарованість» у педагогічній та психологічній літературі Великобританії. Здійснено огляд поняття «обдарованість» в довідниковій літературі – Енциклопедії талановитості, креативності і таланту та Енциклопедії Британіка. Подано концептуальні моделі «обдарованості», які є актуальними для Великобританії, такі моделі як: Г. Гарднера, Дж. Рензуллі, Ф. Монкса, Д. Ейр. Здійснено диференціальний огляд таких понять як «обдарований», «талановитий», «здібний», «дуже здібний». Охарактеризовано основні тенденції дослідження «обдарованоcті» протягом ХХ століття. Диференційовано дослідження «обдарованості» за спадковим та соціальним факторами. В статье рассмотрены определение термина «одаренность» в педагогической и психологической литературе Великобритании. Осуществлен обзор понятия «одаренность» в справочной литературе – Энциклопедии талантливости, креативности и таланта и Энциклопедии Британника. Подано концептуальные модели «одаренности», которые являются актуальными для Великобритании, такие модели как: Г. Гарднера, Дж. Рензулли, Ф. Монкса, Д. Эйр. Осуществлен дифференциальный обзор таких понятий как «одаренный», «талантливый», «способный», «очень способный». Охарактеризованы основные тенденции исследования «одаренности» в течение ХХ века. Дифференцированно исследования «одаренности» по наследственному и социальным факторам. The study of talent is part of the study of individual differences. It is not difficult to conclude that those who are seen as talented are the ones who have had adequate provision to learn and develop their potential. Over the last 100 years thinking in gifted education has developed through three broad phases. In the early to mid-20th century it focused on a small number of unique individuals (Unique Individual Paradigm). The mid to late twentieth century saw the advent of a focus on selecting groups of gifted students from amongst the general school population (Cohort Paradigm). As we moved into the 21st century the focus of leading research has shifted away from identification and towards creating the educational conditions in which ‘giftedness’ might best be developed (Human Capital Paradigm). Two of the most significant, long running and unresolved debates in education are, firstly the issue of how to raise the overall performance of an education system, and secondly how to support the most able pupils within the system. For the most part these debates have been conducted in isolation. It should be noted that in the UK the support of gifted and talented youth at the national level is realized in the framework of the program for talented youth «Young, gifted and talented». The article deals with the definition of «giftedness» in pedagogical and psychological literature of Great Britain. The overview of the concept «giftedness» in The Encyclopedia of Giftedness, Creativity, and Talent and Encyclopedia Britannica is done. Various aspects of «giftedness» are highlighted in the works of contemporary British scientists such as J. Webb, J. Delisle, D. Eyre, H. Gardner, R. Zorman, D. Montgomery, M. Neihart, F. Post, J. Raffan, G. Trost, J. Freeman, K. Heller and many others. Special attention is pointed to the works of J. Freeman, a distinguished psychologist working in the development of human abilities to their highest levels. She has conducted and supervised substantial research, notably her continuing study of gifted children since 1974, and has published widely in this area. For the UK government she has written two major reports and provides advice. The conceptual models of «giftedness», popular in Great Britain, such as of H. Gardner, J. Renzulli, F. Monks, J. Eyre are described. Howard Gardner’s theory of multiple intelligences and Joseph Renzulli’s «three ring» definition of gifted behavior serve as precise examples of multifaceted and expanded conceptualizations of intelligence and giftedness. Gardner’s definition of «giftedness» is «the ability to solve problems, or create products, that are valued within one or more cultural settings». Within his theory, he articulates at least seven specific intelligences: linguistic, musical, logical-mathematical, spatial, bodily-kinesthetic, interpersonal, and intrapersonal. Gardner believes that people are much more comfortable using the term «talents» and that «intelligence» is generally reserved to describe linguistic or logical «smartness»; however, he does not believe that certain human abilities should arbitrarily qualify as «intelligence» over others. Renzulli’s definition, which defines gifted behaviors rather than gifted individuals, is composed of three components as follows: Gifted behavior consists of behaviors that reflect an interaction among three basic clusters of human traits-above average ability, high levels of task commitment, and high levels of creativity. Individuals capable of developing gifted behavior are those possessing or capable of developing this composite set of traits and applying them to any potentially valuable area of human performance.